Archetypes and individuals: reconstructing the users of the Westminster statute staple court, 1485-1532 - Ingram, Hannah Ruth (2019)
This research aims to reconstruct the individual participants of the Westminster statute staple court between the years 1485 and 1532. It relies upon the insights of the certificates of statute staple, as well as a range of other supplementary materials, such as subsidy records, extents for debt and wills, so as to analyse these individuals through a dual statistical and prosopographical methodology. In terms of key research questions, this project seeks to identify the defining social, cultural and economic characteristics relating to these individuals, both on a collective and an individual scale. It engages with important debates surrounding status, social transition and careerism. A dual methodological focus is adopted throughout, whereby statistical analysis of the wider, collective trends relating to these individuals is rendered in deeper, humanising detail through the use of prosopographical exemplars. Indeed, such reconstructive efforts are included in each chapter, highlighting the lives, activities and careers of selected individuals in especial detail, so as to demonstrate both the archetypal characteristics of these people, but also important points of difference. As a whole, this project comprises six main research chapters, each examining a particular key aspect of the lives of the individuals discernible within the certificates of the Westminster statute staple. As prosopography emphasizes the reconstructive, collective narrative of groups of people, the themes and structure of the thesis will broadly reflect this, exploring their lives chronologically as well as thematically.